2019
DOI: 10.1161/circulationaha.118.033552
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia-Driven Inhibition of AMP-Activated Protein Kinase α2 Induces Diabetic Cardiomyopathy by Promoting Mitochondria-Associated Endoplasmic Reticulum Membranes In Vivo

Abstract: Background FUN14 domain containing 1 (Fundc1), an outer mitochondrial membrane protein, is important for mitophagy and mitochondria‐associated endoplasmic reticulum (ER) membranes (MAMs). The roles of Fundc1 and MAMs in diabetic hearts remain unknown. The aims of this study therefore, were to determine if the diabetes‐induced Fundc1 expression could increase MAM formation, and whether disruption of MAM formation improves diabetic cardiac function. Methods Levels of FUNDC1 were examined in the hearts from diabe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
198
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(203 citation statements)
references
References 77 publications
4
198
1
Order By: Relevance
“…Moreover, involvement of MAMs (where FUNDC1 may reside) adds the complexity of FUNDC1 biological function in different disease settings. MAMs display distinct roles in various pathological settings, with enrichment of MAMs being detrimental in metabolic diseases ( 20 , 34 ), whereas MAMs exert cardioprotection in heart failure ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, involvement of MAMs (where FUNDC1 may reside) adds the complexity of FUNDC1 biological function in different disease settings. MAMs display distinct roles in various pathological settings, with enrichment of MAMs being detrimental in metabolic diseases ( 20 , 34 ), whereas MAMs exert cardioprotection in heart failure ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…More interestingly, the expression of FUN14 domain containing 1 (Funcd1), an outer mitochondrial membrane protein important for mitophagy and MAMs, was increased in cardiac tissue from diabetic patients. In STZ-induced diabetic mice, increased Funcd1 induced MAM formation, increased mitochondrial Ca 2+ influx and, subsequently, mitochondrial dysfunction, resulting in diabetic cardiomyopathy [89]. These observations suggest that the structural and functional interactions between the ER and mitochondria have a fine line between being beneficial and being detrimental and should, therefore, be precisely regulated.…”
Section: Alterations Of Interactions Between the Er And Mitochondria mentioning
confidence: 94%
“…Previous findings demonstrated that mitochondrial structure and function are significantly impaired in the islets and muscles of diabetic animals. [28][29][30] Mitochondria also exhibited diminished biogenesis; defective oxidative phosphorylation (OXPHOS); and reduced expression of complexes I, III, and V of the electron transport chain in STZ-treated myocardium tissue or HG-induced cardiomyocytes, [30][31][32] suggesting the impairment and dysfunction of mitochondria in hyperglycemic hearts. Based on TEM analysis, we found that the mitochondrial volume density was not remarkably altered, but that the mitochondria from HG-induced H9c2 cells exhibited significant morphological defects, including mitochondrial vacuolization and destroyed cristae and membranes ( Figure 1E).…”
Section: Mitochondrial Biogenesis and Disorder Were Impaired In Hg-mentioning
confidence: 99%